Analysis of the Impact of Infrastructure Development on Economic Growth in Eastern Indonesia - Nur Nadya T. Balahanti; Irawati Abdul; Boby Rantow Payu (STIE Amkop Makassar, 2026)
Economic growth is understood as a continuous process towards better economic conditions, reflected in increasing output per capita in the long term and is known as part of the concept of *Modern Economic Growth*. This study uses a quantitative approach with an associative-causal design to examine the effect of education, health, electricity, and water infrastructure on economic growth in Eastern Indonesia. Secondary data were obtained from BPS, including indicators of education, health, Susenas, and GRDP ADHK in 13 provinces during the 2020–2023 period. The analysis was conducted through panel data regression using Stata software, with the model selection stage through the Chow and Hausman tests to obtain a Fixed Effect Model with cluster-robust standard errors as the best model. The estimation results show high explanatory power with an R² value of 0.72 and a significant F test, so that all independent variables simultaneously affect economic growth. Partially, education and health infrastructure have negative and insignificant coefficients, indicating that the benefits of both are more long-term and are influenced by the quality of graduates, job market compatibility, and increased labor productivity. Electricity infrastructure shows a significant positive impact at the 10 percent level, although it remains limited due to the dominance of the primary sector and small-scale businesses. Meanwhile, drinking water infrastructure is considered the strongest variable, with a significant positive impact at the 5 percent level, due to its ability to improve public health, reduce household time and costs, and directly boost productivity and economic activity.